Nonpolypoid colorectal neoplasms: a challenge in endoscopic surveillance of patients with Lynch syndrome - Rondagh, E. J. A.; Gulikers, S.; Gómez-García, E. B.; Vanlingen, Y.; Detisch, Y.; Winkens, B.; Vasen, H. F. A.; Masclee, A. A. M.; Sanduleanu, S. (Endoscopy, 2013)
Background and study aims: Patients with Lynch syndrome may develop colorectal cancer (CRC), despite intensive colonoscopic surveillance. Nonpolypoid colorectal neoplasms might be a major contributor to the occurrence of these cancers. The aim of this case – control study was to compare the endoscopic appearance of colorectal neoplasms between patients with Lynch syndrome and control individuals at average risk for CRC.Patients and methods: The endoscopists at the Maastricht University Medical Center were first given training to ensure familiarity with the appearance and classification of nonpolypoid lesions. Patients with Lynch syndrome and patients at average risk for CRC who underwent elective colonoscopy at the Center were prospectively included. Nonpolypoid lesions were defined as lesions with a height of less than half the diameter, and advanced histology was defined as the presence of high grade dysplasia or early cancer.Results: A total of 59 patients with Lynch syndrome (mean age 48.7 years, 47.5 % men) and 590 matched controls (mean age 50.2 years, 47.5 % men) were included. In patients with Lynch syndrome, adenomas were significantly more likely to be nonpolypoid than they were in controls: 43.3 % vs. 16.9 % (OR 3.60, 95 %CI 1.90 – 6.83; P < 0.001). This was particularly true for proximal adenomas: 58.1 % vs. 16.3 % (OR 6.93, 95 %CI 2.92 – 16.40; P < 0.001). Adenomas containing advanced histology were more often nonpolypoid in patients with Lynch syndrome than in controls (4/5, 80.0 % vs. 5/17, 29.4 %; P = 0.19). Serrated polyps were also more often nonpolypoid in patients with Lynch syndrome than in controls: 49.2 % vs. 20.4 % (OR 3.57, 95 %CI 1.91 – 6.68; P < 0.001).Conclusions: In patients with Lynch syndrome, colorectal neoplasms are more likely to have a nonpolypoid shape than those from average risk patients, especially in the proximal colon. These findings suggest that proficiency in recognition and endoscopic resection of nonpolypoid colorectal lesions are needed to ensure colonoscopic prevention against CRC in this high risk population.